EMPOWERING NON-NATIVE ENGLISH SPEAKING TEACHERS THROUGH CRITICAL PEDAGOGY - Nur Hayati (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: Critical pedagogy is a teaching approach that aims to develop studentsâ critical thinking, political and social awareness, and self esteem through dialogue learning and reflection. Related to the teaching of EFL, this pedagogy holds the potential to empower non native English speaking teachers (NNESTs) when incorporated into English teacher education programs. It can help aspiring NNESTs to grow awareness of the political and sociocultural implications of EFL teaching, to foster their critical thinking on any concepts or ideas regarding their profession, and more importantly, to recognize their strengths as NNESTs. Despite the potential, the role of critical pedagogy in improving EFL teacher education program in Indonesia has not been sufficiently discussed. This article attempts to contribute to the discussion by looking at a number of ways critical pedagogy can be incorporated in the programs, the rationale for doing so, and the challenges that might come on the way.